Museum preservation and conservation of cultural heritage in the Northern Region of Peninsula Malaysia - Abu Talib Ahmad, (Universiti Kebangsaan Malaysia, 2010)
This article discusses myriad of museums that are located in the northern region of peninsula Malaysia and their efforts in the preservation and conservation of cultural heritage. The study adopts the historical approach but with a tinge of cultural anthropology while the research methodology is based on museum visits, a scrutiny of publications and pamphlets issued by museums and discussion with those closely associated with museums. Besides the dominance of Malay culture museum efforts of preservation and conservation of cultural heritage including royal ceremonies are selectively undertaken. Certain aspects of Malay culture are marginalized just like the cultural heritage of other ethnic groups. Then there is competition within and among museums. This competition is an extension of the political competition which had existed since 1957